2004
DOI: 10.1007/s11302-004-4741-8
|View full text |Cite
|
Sign up to set email alerts
|

Conserved lysine 79 is important for activity of ecto-nucleoside triphosphate diphosphohydrolase 3 (NTPDase3)

Abstract: Cell membrane-bound ecto-nucleoside triphosphate diphosphohydrolases (NTPDases) are homooligomeric, with native quaternary structure required for maximal enzyme activity. In this study, we mutated lysine 79 in human ecto-nucleoside triphosphate diphosphohydrolase 3 (NTPDase3). The residue corresponding to lysine 79 in NTPDase3 is conserved in all known cell surface membrane NTPDases (NTPDase1, 2, 3, and 8), but not in the soluble, monomeric NTPDases (NTPDase5 and 6), or in the intracellular, two transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Differences in sequence, secondary and tertiary structure are believed to account for differences in catalytic properties between related NTPDases [ 35 ]. The essential role of the ACRs for catalytic activity has been underpinned by a considerable number of studies using point mutations in the ACRs or ACR deletions [ 2 , 29 , 45 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sequence, secondary and tertiary structure are believed to account for differences in catalytic properties between related NTPDases [ 35 ]. The essential role of the ACRs for catalytic activity has been underpinned by a considerable number of studies using point mutations in the ACRs or ACR deletions [ 2 , 29 , 45 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding lysine in human NTPDase3 is K79 and similar results were obtained with the K79A and K79R mutants. Basu et al suggested that a positively charged amino acid in the vicinity of the conserved glycosylation site (N81) of human NTPDase3 is necessary for ConA binding [198]. The effect of mutating this conserved asparagine was studied in three enzymes: rat NTPDase1 [42], human NTPDase2 [43], and human NTPDase3 [40].…”
Section: Mutagenesis Studies Of Cell Surface Ntpdasesmentioning
confidence: 99%
“…The importance of lysine residue 79 located near the conserved glycosylation site near ACR1 was investigated [14]. This residue is conserved in cell surface NTPDases (NTPDase1–3, 8), but not in the soluble (NTPDase5–6) and intracellular (NTPDase4, 7) members of this nucleotidase family (see Table 1 in [14]).…”
Section: Site-directed Mutagenesis Studies (Point Mutations) Of Ntpdasesmentioning
confidence: 99%
“…This residue is conserved in cell surface NTPDases (NTPDase1–3, 8), but not in the soluble (NTPDase5–6) and intracellular (NTPDase4, 7) members of this nucleotidase family (see Table 1 in [14]). All substitutions at this site resulted in a loss of 70%–80% of activity.…”
Section: Site-directed Mutagenesis Studies (Point Mutations) Of Ntpdasesmentioning
confidence: 99%